2014
DOI: 10.5626/jcse.2014.8.2.107
|View full text |Cite
|
Sign up to set email alerts
|

Asymmetric RTS/CTS for Exposed Node Reduction in IEEE 802.11 Ad Hoc Networks

Abstract: One interesting problem regarding wireless local area network (WLAN) ad-hoc networks is the effective mitigation of hidden nodes. The WLAN standard IEEE 802.11 provides request to send/clear to send (RTS/CTS) as mitigation for the hidden node problem; however, this causes the exposed node problem. The first 802.11 standard provided only two transmission rates, 1 and 2 Mbps, and control frames, such as RTS/CTS assumed to be sent at 1 Mbps. The 802.11 standard has been enhanced several times since then and now i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 11 publications
0
11
0
Order By: Relevance
“…Thus, node C is known as the exposed node in this scenario and has to hold its transmission for the Network Allocation Vector (NAV) period defined in the RTS frame. This decreases network spatial utilization and performance [6].…”
Section: Exposed Node Problemmentioning
confidence: 99%
See 4 more Smart Citations
“…Thus, node C is known as the exposed node in this scenario and has to hold its transmission for the Network Allocation Vector (NAV) period defined in the RTS frame. This decreases network spatial utilization and performance [6].…”
Section: Exposed Node Problemmentioning
confidence: 99%
“…Our first research of the proposed method was reported in [6]. However, the research in [6] focused primarily on multi-rate transmission of RTS and CTS frames in order to control transmission range.…”
Section: Related Workmentioning
confidence: 99%
See 3 more Smart Citations